The Effect of Teacher-Made Vocabulary Exercises in Instagram Stories on Students' Vocabulary Achievement - Anisah, Siti; Wahjuningsih, Eka; Puspa, Areta (English Department, Universitas Negeri Surabaya, 2023)
This research aimed to test whether or not teacher-made vocabulary exercises in Instagram stories have a significant positive effect on students’ vocabulary achievement. Therefore, a quasi-experimental research design was applied. The researcher conducted this study during the Ramadhan period with 48 students as the sample participants. They were divided into two groups, experimental and control groups. The researcher taught each group in about two meetings, and most of the time was dedicated to the students to learn vocabulary. They learned vocabulary by doing an exercise provided by the researcher. However, one thing that made them different was the treatment. In learning vocabulary, teacher-made Instagram stories were used as the treatment for the experimental group, while the control group only used the regular tests. After that, all groups did a post-test in the form of multiple-choice. Based on the post-test result, the experimental group gained a mean score of 61.25 and 76.87 for the control group. Then, the researcher used SPSS to analyze the data by employing an independent sample t-test to make a valid conclusion. The result showed that the value of Sig. 2-tailed was lower than 0.05 (0.001<0.05), indicating a significant difference in mean score between the experimental and control group. However, the t value was negative (-3.476). It means that there is no significant positive effect of using teacher-made vocabulary exercises in Instagram stories on students’ vocabulary achievement. Keywords: Instagram stories, vocabulary achievement, TELL